Chemical constituents from Maytenus hookeri. (October 2022) - Jiang, Nian; Yu, Changyan; Hui, Jing; Xie, Jianxun; Wang, Yuanyuan; Yang, Jun; Li, Sanhua; Meng, Lingjie
Abstract: A phytochemical investigation on the branches of Maytenus hookeri resulted in the isolation and identification of fourteen compounds, including one new triterpene saponin (1 ), five phenylpropanoids (2 –6 ), and eight lignans (7 –14 ). The chemical structures of these compounds were determined by comprehensive spectroscopic data analysis, such as UV, IR, 1D/2D NMR, mass spectra, and data from the literature. Furthermore, the chemotaxonomic significance of the isolates was discussed in detail. Highlights: Fourteen compounds (1 –14 ) were isolated for the first time from M. hookeri. The structure of the new triterpene saponin (1) was established from spectroscopic data. Compounds 2, 6 and 12 –14 were obtained for the first time from genus Maytenus. Chemotaxonomic significance of these compounds was described.